Assessing Staphylococcus aureus in ready to eat (RTE) food and risk assessment of food premises in Putrajaya - Abd Wahab, Shafizi; Mohamad Salleh, Mohammad Ridzuan; Anyi, Ubong; New, Chia Yeung; Othman, Mohhiddin; Toh, Poh See; Chai, Lay Ching; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
This cross sectional study was conducted to determine of the presence of S. aureus in ready-to-eat (RTE) food, food premise sanitation level and the relationship between S. aureus presence in RTE food and the sanitation levels of food premises in the locality of the study. A total of 106 samples of RTE food were analyzed by MPN-PCR and the results confirmed that 56 (53%) samples contained S. aureus. Surveyed by type, cooked RTE food had 50 (45%) of the sample having S. aureus presence compared to raw RTE with only 56 (55%). As for risk assessment, a checklist containing nine (9) main parameters consisting of 40 variables as a basis, was conducted on 53 food premises to determine their sanitation levels. The results revealed that 49 premises (92%) are sanitary while the remaining 4 (8%) were categorized as unsanitary. In terms of risk level, 4 premises (8%) were categorized as ‘high risk’, 26 (49%) ‘moderate risk’, and the remaining 23 (43%) are at ‘low risk’. The study found no significant relationship between the presence of S. aureus in RTE food with the level of sanitation of premises in Putrajaya.